Prospectiva de los perfiles organizacionales de las industrias culturales y creativas (2022)
For the development of the objective, a qualitative methodology was used in which semi-structured interviews were applied to referent specialists validated in Focus Groups, which were carried out with directors and professionals in the field who were inquired about technological and organizational trends and profiles. Occupational skills that will be demanded in the future in the audiovisual and radio sector. The interviews have been carried out in several cities of Colombia, for our case we will present results carried out in the Valle del Cauca in the cities of Cali and Buenaventura, which were carried out to Telepacifico, Señal memoria, Creator of digital content, radio Buenaventura and radio voices from Pacific. I